Tradição e inovação são passos de uma mesma dança?: o convívio multigeracional no ambiente corporativo. - Cavalcante Filho, Pedro Pereira (2020)
Background: A world of increasing complexity and ambiguity requires the existence innovative leaders who can find ways of solving the serious problems that affect individuals, organizations and society. This tumultuous world, brought about by the breakneck speed of transformation, has given rise, among other afflictions, to feelings of anxiety, which are reflected in human relations. At the same time, the world is undergoing a fourth industrial revolution, which envisages far-reaching changes in the way we live, hope, dream, and, more specifically, in the way we work and the very meaning of work itself. Technological advances thus oblige companies to adopt new ways of operating in the market and new strategies for mitigating the impact on relations at work. Some work teams now straddle four generations: Baby Boomers (born between 1946 and 1964), Generation X (1965-1980), Generation Y (1981-1997), and Generation Z (born after 1998). This new configuration of the work force is increasingly posing challenges for managers who are charged with building multigenerational teams to work together to achieve the company’s goals. The aim of the present study is thus to provide an overview of recent developments in business, focusing in particular on multigenerational relations and the pressure exerted by successive industrial revolutions. More specifically, the aim is to historicize the world of work and the major revolutions it has undergone; to map the trends being generated by this coexistence of multiple generations; and to examine the issues caused for the world of work by this succession of industrial revolutions. We thus carried out a qualitative, cross-sectional study guided by cartography. The narrative interviews were conducted online with eight members of staff from two private companies. A field diary was also used to produce narratives, which, together with those of the participants, were used to describe the experience examined by this study. The theories of Gilles Deleuze and Felix Guattari were employed to shed further light on these narratives. Results and Discussion: Six planes of analysis emerged from the interviews: Plane 1 -- Multigenerational Coexistence: signs of conflict; Plane 2 -- Power, Authority and Hierarchy: intergenerational relations; Plane 3 -- Lessons Learnt: the potential of the meeting of generations; Plane 4 -- Technology: generational facilities and difficulties; Plane 5 -- The Shock of the Pandemic and Home-oficce: modes of subjectivization in the wake of COVID 19; The participants indicated that conflicts do exist at work, but are not serious enough to affect the group dynamic. Staffmembers acquire knowledge both formally and informally. It was found that older generations, principally the Baby Boomers, experienced difficulty with new technology, while younger ones, especially Generation Z, exhibited great facility in this regard. The COVID-19 pandemic posed a challenge for staff insofar as their homes were transformed from one moment to the next into a workspace. For some participants, working from home has meant that working hours encroach upon leisure time, meals, and family life. The main characteristics of the companies reported by participants were respect for managers and peers and intergenerational exchange of experience. Concluding Remarks: although it is often dogmatically stated in the literature that intergenerational relations at work give rise to deleterious conflict, this was not the finding of the present study. In the companies covered here, only low-level conflict was found. Relations with peers and managers are characterized by a working environment pervaded by a healthy corporate culture of co-operation and respect for fellow human beings.